Kasih Merangkul Keberagaman: Persona Ilahi dalam Trinitas menurut Richard dari Santo Viktor - Andreas Bernadinus Atawolo (Veritas : Jurnal Teologi dan Pelayanan, 2022)
The word “person” is generally used to refer to the existence of both humans and God. For humans, being a person means being able to think logically, have self-awareness, make free choices, and therefore be recognized morally and legally. The Christian faith believes in God as a Divine Person. The Dogma of the Trinity teaches faith in God the Father, the Son, and the Holy Spirit, Three Persons of one nature. Christological dogma teaches that Jesus is a Person who has both divine and human natures. However, what is a person? Specifically, what is the Divine Person? The answer to those questions is found not in the Bible but in the philosophical and theological tracts. This article presents Richard of Saint Victor’s argument on the Divine Person. In his De Trinitate, he sees that the definition of the Divine Person can explain the mystery of the Trinity. Richard borrows this existing understanding, especially from that of Boethius. However, he also offers novelty, which is still relevant today, namely the Trinitarian God as a Divine Person with summa caritas, perfect co-love that is unselfish, non-exclusive, and embraces diversity.